Effect of different oral hygiene measures on oral malodor in children aged 7-15 years - Piyusha S Patil; Pallavi Pujar; V V Subbareddy (Wolters Kluwer Medknow Publications, 2015)
Purpose: To evaluate the effect of various oral hygiene measures individually and in combination in reducing oral malodor. Materials and Methods: A total number of 120 children diagnosed as having oral malodor (oral malodor scores 2 and above) were included in the study. Children were then grouped under four oral hygiene categories (tooth brushing, tongue cleaning, mouth rinsing, and a combination group). There were 30 children in each group. The children were asked to perform oral hygiene methods individually and in combination. The children were then reassessed for oral malodor 2 h later. The results were analyzed and compared. Results: Both individual oral hygiene measure or in combination of tooth brushing, tongue cleaning, and mouth rinsing; all were effective in reducing oral malodor. Significant reduction (P < 0.05) in oral malodor was seen when all three oral hygiene measures performed together. Conclusion: Oral malodor was significantly reduced after performing oral hygiene measures individually, but reduced more when used in combination.